2019
DOI: 10.1021/acscatal.9b02165
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Accelerates the Discovery of Design Rules and Exceptions in Stable Metal–Oxo Intermediate Formation

Abstract: Metal−oxo moieties are important catalytic intermediates in the selective partial oxidation of hydrocarbons and in water splitting. Stable metal−oxo species have reactive properties that vary depending on the spin state of the metal, complicating the development of structure−property relationships. To overcome these challenges, we train machine-learning (ML) models capable of predicting metal−oxo formation energies across a range of first-row metals, oxidation states, and spin states. Using connectivity-only f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
123
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(125 citation statements)
references
References 130 publications
1
123
1
Order By: Relevance
“…The emerging area of machine learning (ML)-accelerated high-throughput computational screening 20,21,63−75 has led to exploration of much larger chemical spaces 76,77 over which no one-size-fits-all exchange correlation functional can be expected to be predictive. Our group has developed representations 70,71 for training ML (e.g., artificial neural networks or ANNs) models to predict spin-state ordering to within sub-kilocalorie per mole accuracy of the DFT training data 70,71,78 and demonstrated the use of these models in the design of a range of spin-state-dependent catalytic 75 and materials 63,70−73,78−80 properties. In evaluating such ML model predictions, we treated DFT as the ground truth, despite its limitations in predicting ground-state spin.…”
Section: Introductionmentioning
confidence: 99%
“…The emerging area of machine learning (ML)-accelerated high-throughput computational screening 20,21,63−75 has led to exploration of much larger chemical spaces 76,77 over which no one-size-fits-all exchange correlation functional can be expected to be predictive. Our group has developed representations 70,71 for training ML (e.g., artificial neural networks or ANNs) models to predict spin-state ordering to within sub-kilocalorie per mole accuracy of the DFT training data 70,71,78 and demonstrated the use of these models in the design of a range of spin-state-dependent catalytic 75 and materials 63,70−73,78−80 properties. In evaluating such ML model predictions, we treated DFT as the ground truth, despite its limitations in predicting ground-state spin.…”
Section: Introductionmentioning
confidence: 99%
“…[87] In order to develop designing principles for the methane activation on the metal-organic framework catalysts, Rosen et al performed DFT calculations to understand the structure-activity relationship. [151] The study reveals that the activation energy of the CH scission and the metal-oxi site formation energy have an inverse relationship. Xu et al found that the classical BEP relationship is not sufficient to be used for metal oxide chemistry in the interest of methane activation, thus they have implemented LASSO to identify key descriptors for predicting.…”
Section: Methane Activationmentioning
confidence: 94%
“…In this section, we discuss the applications of fundamental theory and methodology for the conversion of H 2 , O 2 , H 2 O, N 2 , CO 2 , and CH 4 activation. We refer to other refs for in-depth reviews (H 2 , [149][150][151] O 2 , [152,153] H 2 O, [154][155][156] N 2 , [157][158][159][160] CO 2 , [161][162][163] and CH 4 [4,5] ). Here, we focus on the demonstrations of the catalyst design methods such as the Sabatier principle, d-band theory, high-throughput screening, and machine learning for the activation of small molecules discussed above.…”
Section: Applications Of Computational Approaches For Small Molecule mentioning
confidence: 99%
“…197,198 Chemical descriptors, which typically describe catalytic activity and selectivity, are usually employed as input for algorithms. On the homogeneous side, machine learning protocols have been recently employed to uncover metal-oxo intermediates 199 as well as to screen transition metal catalysts for cross-coupling reactions. 200 On the heterogeneous side, García-Muelas and López demonstrated how principal component analyses and regressions provide adsorption energies on metal surfaces from covalent (d-band center) and ionic (reduction potential) descriptors.…”
Section: Summary and Perspectivesmentioning
confidence: 99%